Electrical Induction as Stress Factor for Callus Growth Enhancement in Plumular Explant of Coconut (Cocos nucifera L.) - Neema, M.; Hareesh, G. S.; Aparna, V.; Chandran, K. P.; Karun, Anitha (International Journal of Bio-resource and Stress Management, 2022)
The study was carried out at the Biotechnology Laboratory, Division of Crop Improvement, ICAR- Central Plantation Crops Research Institute, Kasaragod during 2019−2021 to investigate the effect of electric current induction in coconut plumular callus obtained from WCT variety of coconut. Callus induction was observed when the plumules extracted from the embryo were inoculated into Eeuwens Y3 media supplemented with 16.5 mg l-1 2,4-D and 1 g l-1 activated charcoal. An electrical induction set up was developed to induce minute quantity of electric current to the calli. Electric current of 1µA and 2µA was applied to the system continuously as well as for an interval of 1 h day-1 for a month and differences in callus mass before and after treatment were observed. Callus induced with electric current of 2 µA continuously for a month had maximum weight gain followed by callus induced with 1µA current continuously for a month. Here, anode and cathode were inserted into media and callus respectively. In other two treatments where, 1 µA and 2 µA current was inducted into callus for an interval of 1 hday-1 for a month as well as in control where no current was induced significant weight gain was not observed. The study implicates the effect of electric current in cell division of plants and the results suggests that continuous application of weak electric current in range of 1 and 2 µA enhances callus growth in plumular explants of coconut and could be used as a novel strategy for callus multiplication of coconut, a monospecific crop recalcitrant to in-vitro culture.